GOD AS PURE POSSIBILITY AND THE WONDER OF POSSIBILISATION - C.A.M. Hermans (Acta Theologica)
How do we deal with the issue of permanence in time (Augustine), when we simultaneously experience the limits of our capacity to possibilise the future? The article addresses these questions in terms of the coordinates of the concepts of contingency, the priority of possibility, and free will. It is necessary to rethink theological concepts within these coordinates that are considered characteristic for the self-understanding of modern people. The article describes the development of subjectivity as natality, being capable, and being seen. The aim of this development is to be able to create new beginnings that make the good life with, and for others possible, and give permanence in time. What do we need to think and presume to be vital, for the wonder of possibilisation to emerge? God is imagined as the silent power of the possible (“Can” itself) that keeps in reserve the wonder of possibilisation (“You can”).